Penerapan Model Quantum Teaching Berbantuan Quizizz Dalam Meningkatkan Hasil Belajar Siswa Kelas XI Pada Mata Pelajaran Ekonomi - Lestari, Putri; Gumilar, Gugum; Widyaningrum, Bakti (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research is motivated by the problems that occur in SMA Negeri 1 Tasikmalaya, namely the low student learning outcomes in economic subjects. The purpose of this study was to determine the effect of the Quantum Teaching learning model assisted by Quizizz media on student learning outcomes in economics class XI SMA Negeri 1 Tasikmalaya. This study uses quantitative methods with quasi-experimental design desaigns. The population in this study were all XI grade students of SMA Negeri 1 Tasikmalaya which amounted to 475 students, the research sample of class XI-10 as an experimental class of 38 students and class XI-11 as a control class consisting of 38 students. The data collection technique used is conducting Pretest and Posttest consisting of 25 items with alternative multiple choice answers. Based on the results of the study, it explains that there is a significant difference in improving student learning outcomes using the Quantum Teaching learning model assisted by Quizizz media on the material of economic growth and development, where the average posttest value is superior to the average posttest value using the Discovery Learning learning model, thus it can be concluded that the Quantum Teaching learning model assisted by Quizizz media can improve student learning outcomes.